ChemInform Abstract: Na4IrO4: Square‐Planar Coordination of a Transition Metal in d5 Configuration Due to Weak On‐Site Coulomb Interactions. Issue 28 (July 2015) - Kanungo, Sudipta; Yan, Binghai; Merz, Patrick; Felser, Claudia; Jansen, Martin
Abstract The title compound is prepared via the azide/nitrate route employing a 10:2:3 mixture of NaN3, NaNO3, and IrO2 under Ar (pressed pellets, steel vessel with Ag inlay, 600 °C, 50 h).